Peptidomimetic nitrile warheads as SARS-CoV-2 3CL protease inhibitors. Issue 10 (1st September 2021) - Bai, Bing; Arutyunova, Elena; Khan, Muhammad Bashir; Lu, Jimmy; Joyce, Michael A.; Saffran, Holly A.; Shields, Justin A.; Kandadai, Appan Srinivas; Belovodskiy, Alexandr; Hena, Mostofa; Vuong, Wayne; Lamer, Tess; et al.
Abstract : This article describes peptidomimetic SARS-CoV-2 3CL pro inhibitors with a nitrile warhead with in vitro antiviral inhibition. Superior selectivity was observed for the nitrile warhead compared to the aldehyde against 3 human cathepsins (B, S and L). Abstract : Tragically, the death toll from the COVID-19 pandemic continues to rise, and with variants being observed around the globe new therapeutics, particularly direct-acting antivirals that are easily administered, are desperately needed. Studies targeting the SARS-CoV-2 3CL protease, which is critical for viral replication, with different peptidomimetics and warheads is an active area of research for development of potential drugs. To date, however, only a few publications have evaluated the nitrile warhead as a viral 3CL protease inhibitor, with only modest activity reported. This article describes our investigation of P3 4-methoxyindole peptidomimetic analogs with select P1 and P2 groups with a nitrile warhead that are potent inhibitors of SARS-CoV-2 3CL protease and demonstrate in vitro SARS-CoV-2 antiviral activity. A selectivity for SARS-CoV-2 3CL protease over human cathepsins B, S and L was also observed with the nitrile warhead, which was superior to that with the aldehyde warhead. A co-crystal structure with SARS-CoV-2 3CL protease and a reversibility study indicate that a reversible, thioimidate adduct is formed when the catalytic sulfur forms a covalent bond with the carbon of the nitrile. This effort also identified efflux as a property limiting antiviral activity of these compounds, and together with the positive attributes described these results provide insight for further drug development of novel nitrile peptidomimetics targeting SARS-CoV-2 3CL protease.